PENGARUH SIKAP KERJA, KEMAMPUAN DIRI DAN STRES KERJA TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DAERAH KOTA PADANGSIDIMPUAN - Syawan Sani Siregar; Andi Zuanda; Muhammad Kholidin Hasibuan; Afrianny .; Desviani Yulinda Yusuf (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
Problem of this study is how influence of  job attitude on  employee’s performance. How influence of self ability on  employee’s performance. How influence of  job stress on  employee’s performance. How influence  job attitude, self ability and self ability on  employee’s performance. The purpose of this study to determine and analyze the effect of job attitude on employee’s performance. Determine and analyze the effect of self ability on  employee’s performance. Determine and analyze the effect of job stress on  employee’s performance. Determine and analyze the effect job attitude, self ability and job stress on employee’s performance. Sample in the study is 52 people. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate  job attitude variable has a positive and significant effect on  employee’s performance. Self ability variable has a positive and significant effect on  employee’s performance. Job stress variable has a positive and significant effect on  employee’s performance. Job attitude, self ability and  job stress variable has a positive and significant effect on  employee’s performance.